Evaluación de la estabilidad de emulsiones creadas a partir del aceite de la palma canangucha y diferentes concentraciones de surfactantes (2017)
"The plant diversity of amazonian region offers an opportunity to the development of new technologies for the cosmetics industry. However, the study has its limitations because those plants are part of the heritage of a native population. For this reason, this work investigates and evaluates the behaviour of emulsions made with oil of the amazonial palm "Canangucha". For the study of the required Hydrophilic-Lipophilic Balance (HLB) it is used Tween 80 and Span 20 as surfactants. First of all, it is presented the method of solid-liquid extraction of the oil. Then, the formulation and emulsification of seven emulsions with different values of HLB is described. The stability study was performed with the Turbiscan Stability Index (TSI), the backscattering, and the droplet size." -- Tomado del Formato de Documento de Grado.